ADK, UBK, DAN POTENSI EKONOMI LOKAL: STUDI KASUS DI KABUPATEN KUTAI BARAT - Hermada Dekiawan (Akademi Akuntansi YKPN Yogyakarta, 2010)
This paper discusses the problems of Village Fund Allocation (ADK) and Village Joint Venture (UBK) relation to the potential of local economies in West Kutai District (Kubar). ADK and UBK is one of the components derived from the policy of the Village Fund Allocation (ADD) as set forth in the Act and Regulation of the Minister. In both these legal products, ADD requires local governments to allocate funds for community empowerment sebaian village, with several criteria. However, in practice the policy of ADD cause multiple interpretations, so that the order to each region has different implementations in the policy of ADD, including Kubar. In this paper, will study the implementation of ADK / UBK Kubar relation to local economic potential. Local economic potential Kubar identified by using the weighting, so that the condition information is obtained, which are classified into 3 groups: developed, developing, and growing. The study shows that policies ADK / UBK did not refer to the criteria of the area, so the impact ADK / UBK in economic development Kubar not optimal. On the basis of this, the policy ADK / UBK needs to be associated with the potential of the region, to be more effective in promoting community economic empowerment.Keywords: ADK, UBK, Kutai Barat, Local Economic Development